2020
DOI: 10.1021/acsomega.0c03135
|View full text |Cite
|
Sign up to set email alerts
|

High Ethanol Concentration (77 g/L) of Industrial Hemp Biomass Achieved Through Optimizing the Relationship between Ethanol Yield/Concentration and Solid Loading

Abstract: In this study, the relationships between ethanol yield/concentration and solid loading (6–21%) were investigated to enhance ethanol titer and avoid a random choice of solid loading for simultaneous saccharification and fermentation (SSF). Alkali-pretreated hemp biomass was used for SSF in four scenarios including Case I: 30 filter paper unit (FPU)-cellulase and 140 fungal xylanase unit (FXU)-hemicellulase/g-solid; Case II: 40 FPU-cellulase and 140 FXU-hemicellulase/g-solid; Case III: 30 FPU-cellulase and 140 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…For example, the formation of furfural (0.10-0.25 g/L) and HMF (0.15-0.35 g/L) was reported with hemp after dilute acid pretreatment (1 and 2% H 2 SO 4 ) at 180 • C for 10 min [27]. Dilute alkali pretreatment performed with NaOH was also reported in several previous studies [25,27,28,57]. Alkali pretreatment prevents unwanted sugar degradation by neutralizing released acids during the decomposition of cellulose and hemicellulose by the hydroxide ions from NaOH.…”
Section: Pretreatment Strategies For Industrial Hempmentioning
confidence: 56%
See 3 more Smart Citations
“…For example, the formation of furfural (0.10-0.25 g/L) and HMF (0.15-0.35 g/L) was reported with hemp after dilute acid pretreatment (1 and 2% H 2 SO 4 ) at 180 • C for 10 min [27]. Dilute alkali pretreatment performed with NaOH was also reported in several previous studies [25,27,28,57]. Alkali pretreatment prevents unwanted sugar degradation by neutralizing released acids during the decomposition of cellulose and hemicellulose by the hydroxide ions from NaOH.…”
Section: Pretreatment Strategies For Industrial Hempmentioning
confidence: 56%
“…It can be attributed to the re-condensation of disrupted lignin in case of acid pretreatment, whereas alkali pretreatment unlocks small lignin units [58]. Similarly, in another study, dilute alkali pretreatment performed with 1% NaOH at 170 • C for 30 min increased the glucan content from 40.7% in the raw biomass to 77.5% in the pretreated biomass, with a reduction in lignin from 15.74% to 11.05% after pretreatment [28]. Wawro et al also reported an increase in cellulose content of hemp from 50.8% to 62.7% by NaOH pretreatment (1.5 to 3% NaOH at 90 • C for 5 h) [57].…”
Section: Pretreatment Strategies For Industrial Hempmentioning
confidence: 82%
See 2 more Smart Citations
“…After the alkaline treatment, this band disappears completely or significantly loses its intensity, which may indicate a reduction in both lignin and pectin. Going to the lower wavenumber values, the following three more characteristic bands for the cellulose molecule appear: 1160 cm −1 (asymmetric C–O–C stretching vibrations), 1110 cm −1 (C–OH skeletal vibrations) and 1050 cm −1 (C–O–C skeletal vibrations of the pyranose ring) [ 27 ]. These bands, despite the increase in cellulose content after chemical treatment, are reduced.…”
Section: Resultsmentioning
confidence: 99%